epiArt: a graphical HLA eplet amino acid repertoire translation reveals the need for an epitope driven revision of allele group nomenclature - Doxiadis, Ilias; Lehmann, Claudia; Lachmann, Nils; Loeffler-Wirth, Henry (Frontiers in Genetics, 2024)
The immune response after transplantation depends on recipient/donor HLA allele mismatches. To enhance our understanding of the relations of HLA alleles in terms of amino-acid polymorphisms and shared epitopes, we assessed pairwise sequence difference between HLA-alleles. We translated amino-acid sequences of confirmed eplets into an atlas of HLA class I and II antigens, followed by visualization of the pairwise allele distances by means of antigen-specific disparity graphs in differential amino-acid space. We obtained an overview of relationships of all alleles of an antigen, corresponding similarity/dissimilarity structures, outliers, alleles with similarity to different antigen groups. Additionally, we calculated prevalence of the amino-acids for each polymorphic sequence position and visualized them in amino-acid motif plots of all alleles belonging to an antigen. Our visualizations show strongly varying intra-group heterogeneity of HLA class I and II alleles, as well as shared inter-group and inter-locus eplets and epitopes, indicating a benefit of epitope-based transplant matching: Single allele recipient/donor mismatches potentially refer to identical eplets, or to a set of multiple mismatched eplets. This data reveals inconsistencies in the HLA group nomenclature and consequently adds a new level of quality to allocation, motivating the definition of tolerable or taboo mismatches.